2019
DOI: 10.1002/asi.24321
|View full text |Cite
|
Sign up to set email alerts
|

Co‐contributorship network and division of labor in individual scientific collaborations

Abstract: Collaborations are pervasive in current science. Collaborations have been studied and encouraged in many disciplines. However, little is known about how a team really functions from the detailed division of labor within. In this research, we investigate the patterns of scientific collaboration and division of labor within individual scholarly articles by analyzing their co‐contributorship networks. Co‐contributorship networks are constructed by performing the one‐mode projection of the author–task bipartite ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 53 publications
0
3
0
2
Order By: Relevance
“…The latter would refer to the so-called "author credit assessment": the prestige or importance of the author in the collaboration. A recent study published in the Journal of the Association for Information Science and Technology and conducted by Lu et al (2019) aimed to better understand scientific collaboration. These authors concluded that the author's value is granted by the authors' position, either uniformly or differently (Lu et al, 2019;Stallings et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The latter would refer to the so-called "author credit assessment": the prestige or importance of the author in the collaboration. A recent study published in the Journal of the Association for Information Science and Technology and conducted by Lu et al (2019) aimed to better understand scientific collaboration. These authors concluded that the author's value is granted by the authors' position, either uniformly or differently (Lu et al, 2019;Stallings et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The scientific cooperation network is a network that forms naturally during scientific research. It is widely used to study the formation and evolution of collaboration [37][38][39], the measurement of contribution in cooperation [40,41], the influence of cooperative team composition on scientific research performance [18,42], predicting the possible coauthors for scientists [43], etc. In the scientific cooperation network, nodes represent cooperators and links represent cooperation relationships [44].…”
Section: Institution Cooperation Networkmentioning
confidence: 99%
“…Existen diversas hipótesis -no excluyentes-que buscan explicar el aumento en la coautoría (Katz & Martin, 1997;Hollis, 2001;Lu et al, 2019;O'Hagan & Kuld, 2020). La primera tiene que ver con la división del trabajo, según la cual, la coautoría permite aprovechar la especialización de los autores para enfrentar la mayor exigencia e interdisciplinariedad del mundo académico.…”
Section: La Coautoría En Economíaunclassified